2006
DOI: 10.1161/circulationaha.106.636506
|View full text |Cite
|
Sign up to set email alerts
|

Transthoracic Incremental Monophasic Versus Biphasic Defibrillation by Emergency Responders (TIMBER)

Abstract: Background-Although biphasic, as compared with monophasic, waveform defibrillation for cardiac arrest is increasing in use and popularity, whether it is truly a more lifesaving waveform is unproven. Methods and Results-Consecutive adults with nontraumatic out-of-hospital ventricular fibrillation cardiac arrest were randomly allocated to defibrillation according to the waveform from automated external defibrillators administered by prehospital medical providers. The primary event of interest was admission alive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 40 publications
0
23
0
3
Order By: Relevance
“…One randomized study comparing transthoracic incremental monophasic with biphasic defibrillation for out-of-hospital pulseless VT/VF cardiac arrest failed to demonstrate any significant differences in any outcome (LOE 1). 69 A single-cohort study (LOE 3) 70 using the 2000 International Guidelines 71 demonstrated better hospital discharge and neurological survival with biphasic than with monophasic waveforms. However, there were confounding factors in that the intervals between the first and second shocks (of 3-stacked shocks) were shorter with the biphasic defibrillators.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…One randomized study comparing transthoracic incremental monophasic with biphasic defibrillation for out-of-hospital pulseless VT/VF cardiac arrest failed to demonstrate any significant differences in any outcome (LOE 1). 69 A single-cohort study (LOE 3) 70 using the 2000 International Guidelines 71 demonstrated better hospital discharge and neurological survival with biphasic than with monophasic waveforms. However, there were confounding factors in that the intervals between the first and second shocks (of 3-stacked shocks) were shorter with the biphasic defibrillators.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Although ventricular fibrillation or pulseless ventricular tachycardia is regarded as the most treatable presentation of out-of-hospital cardiac arrest because of its responsiveness to shock, 2 most defibrillation attempts do not result in sustained return of spontaneous circulation. 3 Ventricular fibrillation or pulseless ventricular tachycardia commonly persists or recurs after shock, and there is a significant inverse relationship between the duration of ventricular fibrillation or pulseless ventricular tachycardia, or the frequency of acute recurrences, and resuscitation outcome. [4][5][6] Amiodarone and lidocaine are used commonly to promote successful defibrillation of shockrefractory ventricular fibrillation or pulseless ventricular tachycardia and prevent recurrences.…”
mentioning
confidence: 99%
“…[21][22][23][24][25] Although the optimal energy level for defibrillation using any of the monophasic or biphasic waveforms has not been determined, a recommendation for higher initial energy when using a monophasic waveform was weighed by expert consensus with consideration of the potential negative effects of a high first-shock energy versus the negative effects of prolonged VF. The consensus was that rescuers using monophasic defibrillators should give an initial shock of 360 J; if VF persists after the first shock, second and subsequent shocks of 360 J should be given.…”
Section: -Shock Protocol Versus 3-shock Sequencementioning
confidence: 99%